Ranking the river basin planning alternatives using fuzzy approximate reasoning - Othman, Mahmod; Ku-Mahamud, Ku Ruhana; Abu Bakar, Azuraliza (Chiang Mai University, 2004)
This paper proposes a fuzzy evaluation method in ranking the river basin planning and development alternatives under multicriteria environment. The proposed method uses the application of fuzzy membership sets and approximate reasoning to determine the ranking of the alternatives that involves subjectivity, vagueness and imprecise information. The method automatically generates membership function, which summarized the data to develop the multicriteria combination rule. The aim of utilizing the multicriteria combination rule is to capture the main criteria that exist in the alternatives. The proposed method has shown advantages in generalizing the evaluation of the performance achievement where the evaluation process can be conducted consistently with the use of the set degree of membership.